ON A SHAPKAREV’S METHOD OF DIFFERENTIATION AND TRANSFORMATION - Piperevski, Boro M.; Hadzieva, Elena (Matematichki Bilten, 2015)
This paper emphasises the contribution of Prof. Dr. Ilija A. Shapkarev in the field of differential equations, particularly in the existence and construction of polynomial solution of the ordinary differential equation (ODE) of n-th order, or equivalently, of system of n equations of first order. The method that he uses is called the method of differentiation and transformation (MDT). With this paper we give a review of his work and extension of the application of his method.